Physical Fitness Guidance using Electric Vertical Jump and Child-Friendly Socialization in the Taruna Center of Sepeng Jaya Village, Bekasi City - Candra, Juli; Suharjuddin; Fauzan, Ahcmad; Ningrum, Desy Tya Maya; Balqislamy, Arbayna; Sagala, Dear (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service (PKM) activity aims to increase awareness and practice of physical fitness among the Karang Taruna (Youth Organization) in Sepanjang Jaya Village, Bekasi City, through innovative mentoring and socialization of the importance of sports and a child-friendly environment. The identified problems were the lack of knowledge and motivation of Karang Taruna in maintaining fitness, as well as a minimal understanding of the importance of creating child-friendly public spaces. Physical fitness mentoring was carried out using an electric vertical jump tool, a simple but effective innovation for objectively measuring leg muscle explosive power. Then, a Child-Friendly socialization was held to raise awareness that Karang Taruna has a vital role in creating a safe environment. The PKM implementation method uses a socialization, monitoring, and evaluation approach where Karang Taruna members are actively involved in each session. Based on the evaluation results, this PkM activity has had a very positive impact. In terms of physical fitness, there has been a significant increase in the Sepanjang Jaya Village community, with an average "good" category reaching 70%. In addition, community understanding regarding the implementation of child-friendly values ​​has also increased rapidly, with the achievement result being "very good" in the category of 82.5%.